The youth labour market: From education to work before and after the global financial crisis. (February 2020) - Watson, Ian
This article examines labour market outcomes for teenagers and young adults before and after the global financial crisis. Using labour market activity calendar data, I analyse two cohorts of young people – a pre-global financial crisis cohort and a post-global financial crisis cohort – over the period from 2001 to 2016. A life course approach (sequence analysis) is used to track education-to-work transitions over this period. Optimal matching methods and cluster analysis are used to subdivide the cohorts into three distinctive categories. These form the basis for further analysis, including regression modelling. The key issue examined is whether labour market outcomes differed between these two cohorts, and, by extension, between the periods before and after the global financial crisis. In addition, the categorisation is used to examine issues of long-term marginalisation in the labour market. The main labour market outcomes analysed were gaining employment and conditions of employment, specifically underemployment and casualisation. The article concludes that gaining employment significantly deteriorated over this period. Furthermore, while the comparison of global financial crisis cohorts showed no significant differences when it came to underemployment and casualisation, this partly reflected the fact that both of these were already very high among this population of teenagers and young adults.